THE PLANNING OF THE DENTAL IMPLANTATION BY CONE-BEAM COMPUTER TOMOGRAPHY - Пюрик, В. П.; Проць, Г. Б.; Ничипорчук, Г. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Abstract. Problem statement. The success of treatment with the use of internal bone dental implants depends primarily on careful planning and postoperative preparation. The aim of the research is increasing the efficiency of the dental implantation planning through the use of the orthopantomography and the cone-beam computer tomography. Materials and methods. We examined 154 patients with various kinds absence of teeth, acquired defects and deformations of the alveolar bone of the jaws in need of dental implants as well as preimplantation correction shapes and sizes by jaw reconstructive operations. 56 persons held ortho-pantomography, 98 patients – cone-beam computed tomography scanner to Morita. Planning dental implantation results were processed in the program 3D One Volume Viewer. There was conducted detailed moni-toring of surgical implants, implant and prosthetic steps. Results. The planning of the dental implantation by the conebeam computer tomography determinate implantation opportunity of toothless jaw segment in 64,7% of patients, which allowed to perform dental implants without bone and plastic surgery. With orthopantomography on implantation stage in 91.6% of installed high quality osseointegration, which made it possible to establish conditioners gums. 6,3% of patients who were observed average quality osseointegration, were assigned calcium and implantation stage extended to 9 months. In 2,1% of patients determined by the poor quality of osseointegration, which was the basis for the removal of implants. Conclusions. Established that cone-beam computed tomography is highly informative in determining the ability of implantation toothless jaw segment and in detecting complications of dental implants, and little information in determining the degree of osseointegration. Determined that orthopantomography are high in orthopedic implant and dental implantation stages in assessing the degree of osseointegration and at close fitting prosthetic restoration to the gingival margin.